ANALISIS PERKEMBANGAN INDUSTRI TRANSPORTASI ONLINE DI ERA INOVASI DISRUPTIF (STUDI KASUS PT GOJEK INDONESIA) - Ayu Azizah; Popon Rabia Adawia (Universitas Bina Sarana Informatika, 2018)
In the current disruptive era, technological development is developing so rapidly that it encourages the creation of new innovations and ultimately replaces the previous technology. One industry that is experiencing very rapid growth today is in an online-based transportation business. As time goes by, PT Gojek Indonesia as the first company in the field of online transportation has developed rapidly, so researchers are interested in analyzing the development of the online transportation industry in the current disruptive era. In this study researchers used descriptive research methods. Disruptive innovation is a must-have for all industries today. No exception in the online transportation industry even disruptive innovations have a very important role. In order to continue to grow, compete and survive in the industry. In creative industries like this everything can still happen. The main players who have become market leaders and have huge amounts of capital may be toppled against the most disruptive new players and provide the most important value desired or needed by users.